THE USE OF PICTURE BOOKS IN DEVELOPING CRITICAL THINKING IN EARLY CHILDHOOD CLASSES - Clement Peter Kwambaza; Fidel Dassan Gwajekera (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
This study explores the use of picture books in developing students’ critical thinking skills using a qualitative approach with a case study design. Data were collected through in-depth interviews and analyzed thematically to identify patterns in teachers’ perceptions and practices. The findings indicate that teachers recognize the benefits of picture books in enhancing critical thinking, appreciate their cultural relevance, and acknowledge their ability to engage students’ interest. Teachers implement various strategies, such as narrative analysis, theme integration, stimulating predictive skills, connecting stories to real-life experiences, enhancing visual literacy, encouraging creativity, and promoting collaboration. However, despite this awareness, limitations in professional training hinder the optimal implementation of picture books in classroom practice. Therefore, the study recommends the systematic integration of picture books into lesson planning to stimulate discussion and analytical thinking, as well as the provision of continuous professional development to equip teachers with practical strategies for maximizing the use of picture books in fostering students’ critical thinking skills.